ANALISIS PESERTA DIDIK DALAM MENGHADAPI ERA TEKNOLOGI PADA PEMBELAJARAN SOSIOLOGI DI SMA MUHAMMADIYAH 3 PADANG - Indrifa, Silvia Yulianggi; Erningsih; Yatim, Yenita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research uses qualitative research with a descriptive approach. The theory used is behaviorism theory by B.F. Skinner. The informants for this research consisted of sociology subject teachers, students and environmental students with a total of 10 people who were selected using purposive sampling techniques. The data collection techniques used were observation, interviews and document study. Data analysis was carried out using the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions (verification). The results show that overall, students at SMA Muhammadiyah 3 Padang are able to use technology in learning Sociology. However, there are still obstacles in the form of interference from social media, so teacher direction and school policies are needed to ensure technology is used appropriately and productively to support the learning process.